Clinical utility of radioactive seed localization in nonpalpable breast cancer: A retrospective single institutional cohort study. (December 2018) - Aljohani, Badria; Jumaa, Klaudia; Kornecki, Anat; Brackstone, Muriel
Abstract: Background: With advances in mammographic screening techniques, it has become easier to detect nonpalpable breast lesions at an early stage. Pre-surgical localization of lesions by radioactive seed localization (RSL) has several benefits over conventional wire localization (WL) in guiding breast conserving surgery. In this study, we compared WL and RSL, focusing on the relationship between the techniques and in-breast recurrence or margin positivity. Methods: This study included 1083 patients with nonpalpable breast lesions who underwent breast conserving surgery between 2010 and 2015. The patients were classified into WL and RSL groups. Results: Margin positivity and in-breast recurrence rates did not differ significantly between the WL and RSL groups (P = 0.368 and P = 0.167, respectively). Multivariate analysis showed that tumor grade (OR: 5.016; 95% CI: 1.53–23.059) was significantly associated with margin positivity in patients undergoing RSL. Tumor size was significantly associated with in-breast recurrence in both the WL group (OR: 2.299; 95% CI: 1.561–3.411) and RSL group (OR: 2.998; 95% CI: 1.128–8.043). Conclusion: As the method of tumor localization did not influence margin positivity or in-breast recurrence, either WL or RSL appear to be appropriate for breast conserving surgery. Given the advantages of RSL, including the ability to perform this technique days to weeks before surgery, we propose that high-volume breast centers consider adopting this localization method. Highlights: Non palpable Breast cancer requires pre-surgical localization. Traditional wire localization (WL) has been commonly used to localize the tumor just before surgery. Radioactive seed localization (RSL) is an easy, accurate, and safe technique. Clear surgical margins seem to be crucial factors for survival. No significant differences in margin positivity or local recurrence based on the type of localization method.